Global Agenda for Social Work and Social Development: Voices of the social work educators from Asia. (July 2014) - Nikku, Bala Raju; Pulla, Venkat
Social work is contextual yet increasingly internationalized. The development of Global Agenda in 2012 by the IASSW, ICSW and IFSW gave educators and practitioners an opportunity to reflect on challenges of social work education and the profession in their respective countries. The current article discusses the key factors that confront and influence social work education and practice in the Asian region. The article brings out deep-rooted perceptions amongst educators in the region. The authors endeavour to present select views of social work educators from South Asian countries and suggest possible steps to realize the four goals of Global Agenda in the context of those countries.